Chemogenetic silencing of sensory neuron populations to uncover their role in touch and pain - Middleton, SJ (2020)
The ability of humans to experience touch and pain sensation is critical for our survival. The experience of pain is typically a protective mechanism, and ensures we avoid dangerous environmental cues. However, following incidences of genetic mutations, injury or disease of the somatosensory nervous system, protective pain can become pathological. Indeed, neuropathic pain affects seven to ten percent of the general population, and our current treatment strategies show poor efficacy and tolerability.